Prokineticin Receptor‐1 Is a New Regulator of Endothelial Insulin Uptake and Capillary Formation to Control Insulin Sensitivity and Cardiovascular and Kidney Functions. Issue 5 (23rd October 2013) - Dormishian, Mojdeh; Turkeri, Gulen; Urayama, Kyoji; Nguyen, Thu Lan; Boulberdaa, Mounia; Messaddeq, Nadia; Renault, Gilles; Henrion, Daniel; Nebigil, Canan G.
Abstract : Background: Reciprocal relationships between endothelial dysfunction and insulin resistance result in a vicious cycle of cardiovascular, renal, and metabolic disorders. The mechanisms underlying these impairments are unclear. The peptide hormones prokineticins exert their angiogenic function via prokineticin receptor‐1 (PKR1). We explored the extent to which endothelial PKR1 contributes to expansion of capillary network and the transcapillary passage of insulin into the heart, kidney, and adipose tissues, regulating organ functions and metabolism in a specific mice model. Methods and Results: By combining cellular studies and studies in endothelium‐specific loss‐of‐function mouse model (ec‐PKR1 −/− ), we showed that a genetically induced PKR1 loss in the endothelial cells causes the impaired capillary formation and transendothelial insulin delivery, leading to insulin resistance and cardiovascular and renal disorders. Impaired insulin delivery in endothelial cells accompanied with defective expression and activation of endothelial nitric oxide synthase in the ec‐PKR1 −/− aorta, consequently diminishing endothelium‐dependent relaxation. Despite having a lean body phenotype, ec‐PKR1 −/− mice exhibited polyphagia, polydipsia, polyurinemia, and hyperinsulinemia, which are reminiscent of human lipodystrophy. High plasma free fatty acid levels and low leptin levels further contribute to the development of insulin resistance at the later age. Peripheral insulin resistance and ectopic lipid accumulation in mutant skeletal muscle, heart, and kidneys were accompanied by impaired insulin‐mediated Akt signaling in these organs. The ec‐PKR1 −/− mice displayed myocardial fibrosis, low levels of capillary formation, and high rates of apoptosis, leading to diastolic dysfunction. Compact fibrotic glomeruli and high levels of phosphate excretion were found in mutant kidneys. PKR1 restoration in ec‐PKR1 −/− mice reversed the decrease in capillary recruitment and insulin uptake and improved heart and kidney function and insulin resistance. Conclusions: We show a novel role for endothelial PKR1 signaling in cardiac, renal, and metabolic functions by regulating transendothelial insulin uptake and endothelial cell proliferation. Targeting endothelial PKR1 may serve as a therapeutic strategy for ameliorating these disorders.